IMPLEMENTATION OF TA'ARUF VIEWED FROM ISLAMIC LAW (ON THE ONLINE MARRIAGE BUREAU CV OF BERKAH TA'ARUF PALEMBANG) - Rusmala Dewi; Nurmala HAK; Sara Alvianita (Progressive Law Review, 2023)
One way to get a mate that is done by Muslims is ta'aruf. This ta'aruf process usually begins by exchanging personal biodata or what is known as a CV mediated by a mediator or a third party, namely a teacher, ustadz or ustadzah. Along with the development of the era, the practice of ta'aruf can also be done online. This research aims to find out the perspective of Islamic law on the online ta'aruf process.This research was conducted using a type of field research with a qualitative descriptive analysis method. The approach used is an empirical normative approach. This research was conducted at the Palembang online dating agency CV. The results of the study stated that there were processes that had to be carried out by ta'aruf participants, starting from filling out the form to meeting the parents of both sides of the ta'aruf pair if the ta'ruf was successful. All of these processes are always accompanied by a third party, namely an ustad or ustadzah from Palembang's online dating agency CV. Some of the social media used in Palembang's online dating agencyCV which helps its development, such as Instagram, Whatshaap, Facebook and websites. In the study of Islamic law, the ta'aruf process is appropriate because its implementation is always accompanied until the end, that is, the couple agrees to marry or cancels the ta'aruf. This is done so that each party avoids bad things, such as fraud, adultery or things that are close to adultery and so on.